Quantum mechanic tunneling and efficiency of Faraday current-generating process in porous nanostructures - Lukiyanets, B.A.; Matulka, D.V.; Grygorchak, I.I. (Condensed Matter Physics, 2011)
Thermodynamics and kinetics of lithium intercalation into C-SiO₂ nanocomposites are investigated. Dependencies of both differential capacity and intercalation kinetics on the nanocomposite size are established. The processes are analyzed in terms of the impedance model. The obtained results are explained based on the quantum effect of interference blockade of electron tunneling into a nonmetallic nanoparticle. Propositions for the new electrochemical energy storage technology are presented.